On the Characteristics of a Twin-Jet STOVL Fountain - Saddington, Alistair J.; Knowles, Kevin; Cabrita, P. M. (Cranfield University, 2015)
The interaction of multiple jets with the ground is of great importance for the design and operation of short take-off, vertical landing aircraft. The fountain upwash flow, generated by the impingement of two axisymmetric, compressible, turbulent jets onto a ground plane was studied using laser-based particle image velocimetry and laser Doppler velocimetry. Measurements were made with nozzle pressure ratios of between 1.05 and 4, nozzle height-to-diameter ratios of between 2.4 and 8.4, nozzle splay angles of between 15 degrees and a nozzle spacing-to-diameter ratio of seven. The effect of varying these parameters on the fountain velocity decay, spreading rate and momentum flux ratio are discussed. Mean fountain upwash velocity profiles were found to be self-similar for all test conditions. A distinct frequency of fountain oscillation was identified but only at a nozzle height of 4.4 diameters.
Presented at International powered lift conference London 22-24 July 2008